The conceptual framework of entrepreneur and self management - Lucky, Esuh Ossai-Igwe; Minai, Mohd Sobri (Centre for Promoting Ideas, 2011)
Until now, many entrepreneurs remain ineffective as a result of their inability to manage themselves, which is critical for the entrepreneurs’ personal success and firm performance.Self management has not been explored in both academic and practical field of small business and entrepreneurship discipline.Research in this area has only been focusing on entrepreneurship and time management.This paper is motivated to discuss self management in relation to entrepreneur and small business performance.The paper argues on the crucial role of self management for entrepreneurs’ success and firm performance.It highlights that self management deserves urgent and serious attention in entrepreneurial discourse and should not be neglected. It also provides the way forward to examine self management in relation to entrepreneurs and their business performance.